2022
DOI: 10.3389/fonc.2022.744886
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Effects, Pathways, and Target Molecules of JC Polyoma Virus T Antigen in Cancer Cells

Abstract: JC polyoma virus (JCPyV) is a ubiquitous polyoma virus that infects the individual to cause progressive multifocal leukoencephalopathy and malignancies. Here, we found that T-antigen knockdown suppressed proliferation, glycolysis, mitochondrial respiration, migration, and invasion, and induced apoptosis and G2 arrest. The reverse was true for T-antigen overexpression, with overexpression of Akt, survivin, retinoblastoma protein, β-catenin, β-transducin repeat-containing protein (TRCP), and inhibitor of growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…T antigen knockdown could suppress glycolysis, mitochondrial respiration, proliferation, migration, and invasion in lens tumor cells; however, it promoted apoptosis. T antigen can also activate the Akt/NF-kB/survivin pathway, producing an anti-apoptosis effect and causing Rb hyperexpression and p21 hypoexpression to mediate cell cycle progression (88). These findings suggest that the T antigen can aggravate the cellular phenotype, possibly by inactivating tumor suppressors, activating oncogenes, or disrupting metabolism and cell adhesion.…”
Section: The Signal Pathways Of Jcpyvmentioning
confidence: 97%
See 2 more Smart Citations
“…T antigen knockdown could suppress glycolysis, mitochondrial respiration, proliferation, migration, and invasion in lens tumor cells; however, it promoted apoptosis. T antigen can also activate the Akt/NF-kB/survivin pathway, producing an anti-apoptosis effect and causing Rb hyperexpression and p21 hypoexpression to mediate cell cycle progression (88). These findings suggest that the T antigen can aggravate the cellular phenotype, possibly by inactivating tumor suppressors, activating oncogenes, or disrupting metabolism and cell adhesion.…”
Section: The Signal Pathways Of Jcpyvmentioning
confidence: 97%
“…The upregulated proteins are involved in signaling through Cyclin-CDK, TGF-b receptor 1, fibroblast growth factor family receptor and platelet-derived growth factor receptor and the inflammatory responses mediated by Cox-2 (89). T antigen might interact with ribosomal proteins, various keratins, G proteins, apolipoproteins, ubiquitin-related proteins, CCAAT enhancer-binding proteins, b-catenin, RPL19, b-TRCP, and p53 in lens tumor cells (88). T antigen knockdown could suppress glycolysis, mitochondrial respiration, proliferation, migration, and invasion in lens tumor cells; however, it promoted apoptosis.…”
Section: The Signal Pathways Of Jcpyvmentioning
confidence: 98%
See 1 more Smart Citation
“…Computational methods to find the repurposable drugs targeting the viral cancers use supervised ML and DL methods and make use of the publicly accessible databases 28,44–47 and in‐house information resources. Most studies and methods use the target activity profiles of compounds for informed drug repurposing process 48–50 …”
Section: Introductionmentioning
confidence: 99%
“…Most studies and methods use the target activity profiles of compounds for informed drug repurposing process. [48][49][50] Moreover, a lot of drug repurposing studies using modeling, ML, and DL approaches (Figure 1) have been reported which are focusing on the viral cancers with references to the viruses that cause or increase the risk of cancer. These viruses are infectious microbes which are host dependent parasites and proliferate using host cells.…”
mentioning
confidence: 99%